Design of Visual Identity for the Education Campaign “SiSko-Siaga Skolio” as a Scoliosis Prevention - Birgita Cornelia Sumarga Putri; Aditya Rahman Yani; Aris Sutejo (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2026)
Scoliosis is a spinal disorder characterized by a lateral curvature exceeding 10 degrees and is prevalent among adolescents during growth. Observations and questionnaires indicate that teenagers aged 13–15 continue to engage in habits that pose a risk for scoliosis, such as slouching while seated, utilizing devices with poor posture, and carrying heavy bags on one shoulder. This study seeks to design the educational campaign “SiSko – Scoliosis Alert” as a visual communication tool to raise awareness among Surabaya teenagers regarding the significance of maintaining good posture as a preventive measure against scoliosis. The research methodology employed a qualitative approach through interviews, Focus Group Discussions (FGDs), observations, and questionnaires with teenagers aged 13–15 in Surabaya. The analysis revealed that the majority of teenagers possess an understanding of scoliosis, yet they continue to disregard good posture habits due to comfort and a lack of long-term awareness. Based on these findings, the keyword “Caution That Saves” was formulated as the foundation for developing the verbal and visual concept of the campaign. The campaign design “SiSko – Scoliosis Alert” was realized through visual media such as Instagram feeds, Instagram Stories, posters, and leaflets, employing persuasive and emotional approaches tailored to teenagers’ characteristics.